A proposal to support student therapists to develop compassion for self and others through Compassionate Mind Training. (September 2016) - Beaumont, Elaine; Hollins Martin, Caroline J.
Highlights: Educators are the gatekeepers of the profession and have first-hand knowledge of the stressors faced by student therapists. CMT utilises creative interventions and has the potential to impact upon levels of compassion for self and compassion for others. Cultivating self-compassion may act as a remedy to self-criticism and help students face the demands of practice. Abstract: Purpose: Student therapists can experience incidents in practice interactions that are emotionally rewarding but sometimes highly challenging. In responding to distressing events, they may experience empathic distress fatigue, compassion fatigue, stress, burnout, and self-criticism, which in turn can alter their ability to provide compassion to both self and others, and can create persistent self-criticism and negative rumination. A creative framework designed to teach student therapists about Compassion Focused Therapy (CFT) to underpin the worth of Compassionate Mind Training (CMT), is a training process designed to increase levels of compassion. Expected learning outcomes: On completion of teaching the 6-step study framework, student therapists will understand variables that influence compassion delivered to both self and others. They will understand how the compassionate mind model works, and consider how cultivating compassion can moderate self-critical dialogue. They will gain understanding of the 3 flows of compassion, examine how low levels of compassion can lead to empathic distress fatigue, compassion fatigue, burnout and self-criticism, and explore how emotions, such as shame and self-critical thinking impact upon well-being. Practical implications: The suggested programme will develop the ability in student therapists to 'be kinder to self' in times of stress, hence building their resilience. It is recommended that post-delivery of a well prepared teaching plan that addresses the 6-step study framework, that the lecturing team evaluate the effectiveness of the training.